Complete replacement of the mitochondrial genotype in a Bos indicus calf reconstructed by nuclear transfer to a bos taurus oocyte - Meirelles, Flávio V.; Bordignon, Vilceu; Watanabe, Yeda; Watanabe, Michelle [UNESP]; Dayan, André [UNESP]; Lôbo, Raysildo B.; Garcia, Joaquim M. [UNESP]; Smith, Lawrence C. (My University, 2001)
Due to the exclusively maternal inheritance of mitochondria, mitochondrial genotypes can be coupled to a particular nuclear genotype by continuous mating of founder females and their female offspring to males of the desired nuclear genotype. However, backcrossing is a gradual procedure that, apart from being lengthy, cannot ascertain that genetic and epigenetic changes will modify the original nuclear genotype. Animal cloning by nuclear transfer using host ooplasm carrying polymorphic mitochondrial genomes allows, among other biotechnology applications, the coupling of nuclear and mitochondrial genotypes of diverse origin within a single generation. Previous attempts to use Bos taurus oocytes as hosts to transfer nuclei from unrelated species led to the development to the blastocyst stage but none supported gestation to term. Our aim in this study was to determine whether B. taurus oocytes support development of nuclei from the closely related B. indicus cattle and to examine the fate of their mitochondrial genotypes throughout development. We show that indicus:taurus reconstructed oocytes develop to the blastocyst stage and produce live offspring after transfer to surrogate cows. We also demonstrate that, in reconstructed embryos, donor cell-derived mitochondria undergo a stringent genetic drift during early development leading, in most cases, to a reduction or complete elimination of B. indicus mtDNA. These results demonstrate that cross-subspecies animal cloning is a viable approach both for matching diverse nuclear and cytoplasmic genes to create novel breeds of cattle and for rescuing closely related endangered cattle.
Keywords: animal cell; animal experiment; blastocyst; Bos indicus; Bos taurus; cattle; cross breeding; development; female; gene construct; genotype; male; mating; mitochondrion; molecular cloning; nonhuman; oocyte; priority journal; Animals; Base Sequence; Cattle; Cell Nucleus; DNA Primers; Embryo; Genotype; Mitochondria; Oocytes